Perceptions of Autism Spectrum Disorder among People in a Remote Area of Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2023)
Introduction: Autism is a neurodevelopmental disorder which are manifested within two years of life. It exhibits difficulties in social interaction, verbal and nonverbal communication, as well as repetitive or constrained interests and actions. Autism has already posed significant burden in health sector in Bangladesh. That’s why it is high time to address autism. Objectives: To assess the factors affecting children with ASD and perception of rural people about it.Methods: This cross sectional study was carried out from 01 January to 31 December, 2021 among 55 people of different unions of Bauphal Upazila of Patuakhali district. Results: Majority of the autistic children are male (61.82%). In maximum cases, parents and family members were usually the first persons to identify (60%) the autistic symptoms. A good percentage (21.82%) respondents were ignorant about the cause of autism. Most (38.18%) of the children with autism were treated at government hospital. Maximum therapy received by the children is speech therapy (41.82%) and there is partial improvement (54.55%) of autism by applying therapy.Conclusion: This study revealed that most of the parents of autistic child were unaware about its contributory factors and treatment. Even there is scarcity of trained or specialist health professionals. There are also false belief about autism that inhibit people to take proper treatment.JAFMC Bangladesh. Vol 18, No 2 (December) 2022: 66-71